The Effects of Ply Orientation on Nonlinear Buckling of Aircraft composite Stiffened Panel (Fracture and Structural Integrity, 2019)
In this paper, gradual demand for curved, stiffened panels composite emerged from carbon fiber reinforced plastics (CFRP); these are structures that are frequently used in aerospace engineering. Up to 50% of the primary structure of the Boeing 787 is made up of woven graphite–epoxy. This research emphasizes the buckling analysis of stiffened composite panels using the nonlinear, finite element modeling. The stiffened panel is assumed to be subjected to a uniform axial compression load of . For the nonlinear buckling analysis, a stiffened composite panel is made of carbon fibre composite (CFC) in epoxy, Kevlar in epoxy and E-glass (EG) in epoxy. Due to the fact that there are numerous stiffened composite panels materials, this paper, therefore uses a numerical approach, to present the study and results of the nonlinear static buckling analysis of I-stiffened, on different composite panels. This research also presented the effect of the different ply orientations using Abaqus finite element analysis (FEA).
Keywords: Stiffened composite panels; Nonlinear buckling analysis; FEM ply orientations